Does kappa-carrageenan thermoreversible gelation affect β-carotene oxidative degradation and bioaccessibility in o/w emulsions?. (1st July 2017) - Soukoulis, Christos; Tsevdou, Maria; Yonekura, Lina; Cambier, Sébastien; Taoukis, Petros S.; Hoffmann, Lucien
Highlights: Ionic and coldset κ-carageenan emulsions loaded with β-carotene were fabricated. Ionically mediated o/g emulsions enhanced β-carotene retention during storage. β-Carotene bioaccessibility was higher in coldset o/g emulsions. O/g emulsion colloidal changes throughout digestion depended on gelation method. Digesta containing Ca 2+ underwent aggregative depletion of bile salts. Abstract: In the present work oil-in-gel (o/g) emulsions comprising 0.4–1% w/w κ-carrageenan in the absence and presence of Ca 2+ (20 mM) were investigated for their ability to hamper the oxidative degradation under isothermal (5, 20 and 37 °C) ambient air storage conditions and promote the in vitro bioaccessibility of β-carotene. The mechanical and structure conformational aspects of the o/g emulsions throughout in vitro digestion were measured by means of oscillatory rheology and optical microscopy. Although the addition of κ-carrageenan reduced by more than 50% (from 0.85 to 0.40 day −1 ) the β-carotene oxidative degradation rates, only minor differences were detected in terms of gelation method (ca. 0.42 and 0.39 day −1 for ionotropic and coldset systems) and biopolymer concentration (0.38–0.42 day −1 ). The bioaccessibility of β-carotene was significantly higher in coldset o/g emulsions (ca. 43%) compared to the ionically mediated ones (ca. 36%). With the exception of 0.4% κ-carrageenan containing o/g emulsions (55.4 and 49.7% for control and 0.4% κ-carrageenan respectively), the β-carotene bioaccessibility was significantly reduced with the increase in κ-carrageenan concentration (ranging from 34 to 38.9%).